Low-temperature electrical and dielectric properties and Mössbauer spectra of rutile-type FeNbTiO6, prepared in oxidizing and reducing conditions. (December 2017) - Günther, A.; Hochleitner, R.; Lohringer, H.; Schmidbauer, E.; Schöttler-Himmel, A.; Volk, M.
Abstract: In this communication we present preferentially bulk electrical and dielectric quantities on rutile-type FeNbTiO6 samples below room temperature (RT), sintered in air, CO2 or 5%H2 /CO2 atmosphere between temperatures of 1423 K and 1573 K. In the past, FeNbTiO6 had been found to exhibit relaxor ferroelectric-like dielectric constant peaks at 500–600 K, assigned to bulk properties and to some extent to grain boundary and sample–electrode processes. Below RT, mainly bulk data were collected from impedance spectra; derived quantities describe characteristic features of bulk response for samples prepared in different conditions. The DC electrical conductivity obeys Mott's variable range T −1/4 law between ≈80 K and 220 K for samples sintered at 1573 K in air, as already reported previously, while after heating at 1473 K in air, Arrhenius behavior occurs. The individual samples show characteristic differences as regards DC and AC conductivity, dielectric constant and dissipation factor tanδ. 57 Fe Mössbauer spectroscopy enabled to gain knowledge of local inhomogeneities in the environment of FeO6 octahedra that may affect electrical conduction. This concerns in particular samples, prepared in reducing conditions of H2 /CO2 atmosphere, with Fe 2+ exceeding by far the fraction of Fe 3+ . Highlights: Rutile-type FeNbTiO6 was synthesized in oxidizing and reducing atmosphere. Mössbauer spectra reveal Fe 3+ and Fe 2+ after preparation in reducing condition. Impedance spectra measured at low T enable to determine bulk properties. Electrical DC and AC conductivities are higher after synthesis in reducing condition. The dielectric constant shows a considerable drop towards low T for all samples.